Kolaborasi Penta Helix dalam mendukung Technosociopreneurship: Pendekatan Baru untuk Pertumbuhan Ekonomi Lokal - Swandono, May Agus; Nuzil, Nur Rokhmad; Ajizah, Nur; Huda, MIftahul (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study has the complexity of economic challenges faced by local communities, especially in facing global competition and rapid technological changes. The purpose of this study is to collaborate the Penta Helix Model implemented in supporting technosociopreneurship and the role and contribution of each stakeholder. In achieving this, this study uses a research method used with a Qualitative method. Which includes a literature review, interviews with stakeholders, observations, and case studies. The urgency of this study is due to the large number of MSMEs that have gone bankrupt due to the lack of support from various stakeholders to strengthen technosociopreneurship and increase local economic growth.The results of this study show that the Penta Helix collaboration involving academics, businesses, government, communities, and the media plays an important role in supporting technosociopreneurship in Pasuruan Regency. Academics contribute by providing the necessary knowledge and training, while the business sector plays a role in providing access to capital and markets. The local government acts as a regulator and provider of policies that support the entrepreneurial ecosystem. The community actively participates in helping to connect innovators with local communities. Meanwhile, the media plays a role in disseminating information and promoting technosociopreneurship.